Factors related to dropout in integrative oncology clinical trials: interim analysis of an ongoing comparative effectiveness trial of mindfulness-based cancer recovery and Tai chi/Qigong for cancer health (The MATCH study) - Devesh Oberoi; Katherine-Ann L. Piedalue; Hassan Pirbhai; Steven Guirguis; Daniel Santa Mina; Linda E. Carlson (BMC Research Notes, 2020)
Abstract Objective To examine the factors associated with loss to follow-up (LTFU) in an ongoing preference-based randomized waitlist controlled trial of mindfulness-based cancer recovery (MBCR) and Taichi/Qigong (TCQ) for cancer survivors (the MATCH Study). Hierarchical logistic regression was used to determine the factors associated with LTFU. Predictors included adherence to treatment, preference vs. randomized, type of intervention (MBCR vs. TCQ) and program timing (immediate IM vs. waitlist control WLC group). Results Data indicated that randomization to the WLC group and, once in the intervention, low adherence were the main predictors of LTFU. Participants in the WLC group were 4 times more likely to be LTFU post-randomization [OR 3.96, 95% CI 2.08–7.56, p < 0.005] than those in the IM group. Participants showing low adherence to treatment were 6 times more likely for LTFU post-intervention [5.87 (2.57–13.400; p < 0.005] and 4 times more likely for LTFU 6 months post-intervention [OR 3.93, 95% CI 1.53–10.02, p = 0.01].